ANALISIS PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KERUPUK RUMPUT LAUT UD. HARKAT MAKMUR - STEVANY HANALYNA DETHAN; NI WAYAN PUTU MEIKAPASA; THERESIA SUZANNA CATHARINA (GANEC SWARA, 2022)
This study aimed to find out the price and promotions singinificant effect on purchasing decision kerupuk rumput laut UD. Harkat Makmur in partial or simultan. This associative research study was conducted. The study employed a non probability sampling with insidental sampling technique by involving 50 respondents as the samples. Data analysis method in this study use multiple linier regression analysis. The result  of the study show price and promotions have significant effect on purchasing decision kerupuk rumput laut UD. Harkat Makmur in partial or simultan.